Culture Effects on Language and Cognition in Psycholinguistic Experiment - Zasiekina, Larysa (East European Journal of Psycholinguistics, 2014)
The study is based on two main scientific paradigms – cognitive and discursive. The process of social categorization by American and Ukrainian students has been focused on in a psycholinguistic experiment. Social schemes (personal schemes, action schemes, self-schemes, role schemes, function schemes) in word meanings for words denoting social objects suggested by Ukrainian (n=25, 12 female and 13 male, mean age 21,7±3,0 years, Lesya Ukrainka Eastern European National Universities, Lutsk) and American (n=25, 15 female and 10 male, mean age 22,4±3,0 years, University of Central Arkansas, Conway, USA) students were analyzed. The results of comparative analysis of word meanings based on social categories (schemes) of Ukrainian and American students show that the most frequent social categories among American students are self- schemes, which are connected with individualism of national character of western-culture people. The most frequent social categories among Ukrainian students are action schemes which express pragmatic character of Ukrainian culture. Despite of the various distributions of social schemes in Ukrainian and American students’ answers, the indifferent to culture criteria for social categorization are revealed. The results of psycholinguistic experiment show the dual cognitive and discursive character of social categorization which demonstrates the degree of culture impact on human cognition and language. References Chomsky N. (2002). Syntactic Structures. Berlin: Mouton de Gruyter. Colman, A. (2003). Dictionary of psychology. Oxford: Oxford University Press. Cutler, A. (2005). Twenty-first century psycholinguistics. Mahwah, New Jersey: Lawrence Erlbaum Associates, Publishers. Gould, J.A. (1978). Classic philosophical questions. Columbus: Bell and Howell Company. Gudykunst, W. Lauren I. Gumbs (1989). Social cognition and intergroup communication. New Delhi: Sage Publication. Jackendoff R. (2007). Language, consciousness, culture. Cambridge: The MIT Press. Kiss G., Armstrong C., Milroy R., & Piper, J. (1972). An associative thesaurus of English. Edinburgh: University of Edinburgh. Miller, G. A. (1990). Linguistics, psychologists, and the cognitive science. Language, 66, 2, 317- 322. Toomela, A. (1996). How culture transforms mind: a process of internalization. Journal of Culture and Psychology, 285-305. Peirce, C. S. (1958). Collected Papers of Charles Sanders Peirce. Harvard: Harvard University Press. Rosch, E. (1987). Wittgenstein and categorization research in cognitive psychology. In: Meaning and the growth of understanding. Wittgenstein’s significance for Developmental Psychology, Ed. By M. Chapman & R. A. Dixon. Berlin: Spring-Verlag, 151-167. Schank, R.C. & Abelson, R. (1977). Scripts, Plans, Goals, and Understanding. Hillsdale, NJ: Erlbaum Association. Sternberg, R. J. (1985). Beyond IQ: a triarchic theory of human intelligence. New York: Cambridge University Press. 14. Vygotsky, L.S. (1996). Myshleniye i Rech [Thinking and speech]. Moscow: Labirint.